An Archean atmosphere rich in sulfur biomolecules - Nathan W. Reed; Cade M. Christensen; Jason D. Surratt; Shawn Erin McGlynn; Boswell A. Wing; Cajetan Neubauer; Margaret A. Tolbert; Eleanor C. Browne (Proceedings of the National Academy of Sciences, 2025)
The abiotic production of sulfur-containing biomolecules under mild and globally relevant conditions has been an elusive endeavor in prebiotic chemistry experiments. As a result, a disconnect has emerged between understanding the origins of life and the later stages of biological evolution; the former potentially occurred independent of sulfur while the latter is universally dependent on it. Here, we demonstrate that planetary organic haze chemistry produces a suite of sulfur biomolecules including cysteine, coenzyme M, taurine, and potentially methionine and homocysteine. These compounds may form high in the atmosphere and subsequently deposit to early surface environments in sufficient amounts to support a budding global biosphere. Our findings thus challenge long-standing assumptions that sulfur biomolecules such as cysteine must have been biological “inventions.”